"New" views on the optimum currency area theory: what is EMU telling us? - Francesco Paolo Mongelli (European Central Bank (ECB), 2002)
This paper surveys the optimum currency area (OCA) literature. It is organised into four phases: the 'pioneering phase' which put forward the OCA theory and its properties, the 'reconciliation phase' when its diverse facets were combined, the 'reassessment phase' that led to the 'new OCA theory' and the 'empirical phase' during which the theory was subject to due empirical scrutiny. We make systematic reference to the European economic and monetary union (EMU) to which the OCA theory has been most frequently applied. All pioneering contributions are still relevant. Several early weaknesses have now been amended. Meanwhile, the balance of judgements has shifted in favour of currency unions. They are now deemed to generate fewer costs in terms of the loss of autonomy of domestic macroeconomic policies, and there is greater emphasis on the benefits. Looking ahead we are confronted with two distinct paradigms – specialisation versus endogeneity of OCA.
Keywords: E42; F15; F33; F41; 330; and EMU; Economic and Monetary Integration; International Monetary Arrangements; Optimum Currency Area